On the Exit of One Class of Random Walks from an Interval - Gusak, D. V. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We consider the random walk S_n = _kξ_k (S_n = 0) whose characteristic function of jumps ξ_k satisfies the condition of almost semicontinuity. We investigate the problem of the exit of such S_n from a finite interval.